Genomic characteristics of Mycobacterium tuberculosis isolates of cutaneous tuberculosis - Mei, You-Ming; Zhang, Wen-Yue; Sun, Ji-Ya; Jiang, Hai-Qin; Shi, Ying; Xiong, Jing-Shu; Wang, Le; Chen, Yan-Qing; Long, Si-Yu; Pan, Chun; Luo, Tao; Wang, Hong-Sheng (Frontiers in Microbiology, 2023)
Cutaneous tuberculosis with various manifestations can be divided into several clinical types according to the host immune status and infective route. However, the etiological factors of this disease remain unclear. To investigate the pathogens associated with the occurrence and different types of cutaneous tuberculosis, 58 Mycobacterium tuberculosis strains isolated from cutaneous tuberculosis in the last 20 years were sequenced and analyzed for the genomic characteristics including lineage distribution, drug-resistance mutations, and mutations potentially associated with different sites of infection. This study identified the molecular characteristics of cutaneous infection caused by M. tuberculosis in southeastern China. The strains isolated from the cutaneous tuberculosis had a lower rate of drug resistance. The M. tuberculosis strains from four major types of cutaneous tuberculosis and pulmonary tuberculosis shared similar genotypes and genomic composition. Several SNPs in metabolism related genes exhibited a strong correlation with different infection sites. The different infection sites of TB may barely be affected by large genomic changes in M. tuberculosis isolates, but the significant difference in SNPs of metabolism-related genes still deserves more attention.